'Words have a charge': six moments from a dialogue. (December 2022) - Bhabha, Homi K.; Emerling, Jae
This conversation contains 'moments' from a dialogue between the esteemed scholar Homi K Bhabha and Journal of Visual Culture editor Jae Emerling that took place at Harvard University on 7 March 2022. As part of the 20th anniversary celebrations of the journal's founding, it was essential to include voices whose work, presence within the world, and poetic insights traverse the entirety of visual culture studies. Bhabha is certainly such a voice for our Editorial Collective, past and present. The goal of this open dialogue, if there is a single one, was to have a real conversation about Bhabha's vital current projects, which address the socio-economic, political, and cultural dangers facing all of us. But it is also a hopeful discussion about the 'survival' of the theoretical humanities in the 21st century. We hope that it reads as dialogic-radiating lines passing through the singular points that shape the history of our present, while always remaining open and attentive to the unforeseen actualizations of the past–future events that compose each of us individually and collectively.